METHOD OF DEVELOPMENT OF PRE-SCHOOL CHILDREN’S SPEECH PROSODIC COMPONENT BY MEANS OF VOCAL THERAPY - Bohrova, Khristina (PSYCHOLOGICAL JOURNAL, 2017)
The article considers the comprehensive speech prosodic component`s development of preschool children by means of vocal therapy based on the integrated usage of musical expression means, which are common with components of prosodic, that makes their interaction, relationship and most importantly, influence. The methodology of prosodic component development of preschool children`s speech and technology of its implementation is presented. The specificity of the vocal therapy impact is reasoned and the conceptual apparatus is clarified. The theoretical author's model is developed, which contains the vocal works, which cause the development of speech prosodic component. The components of mentioned blocks are developed according to the proposed species, groups, specifics of manifestation and nature of the vocal therapy influence. The scheme of speech prosodic component development by means of vocal therapy is characterized. It consists of three blocks: two diagnostic (before and after vocal therapy) and one developmental, which causes change of preschool children`s speech components. The criteria of describing the influence of vocal therapy efficiency are indicated: objective (temporal regularities in the usage of musical works) and subjective (expression, activity, dynamic), with regard to development of prosodic component of preschool children`s speech, taking into account individual psychological characteristics, that manifest on three levels: emotional (reduction of anxiety), personal (self-esteem increase, improvement of self-regulation of temperament properties), communicative (improving of group interaction).